Dorsey William Hyde papers - Hyde, Dorsey William, 1888-1955.; Page, Curtis Hidden, 1870-1946.
Correspondence, memoranda, diaries, speeches, writings, articles, genealogical and biographical material, scrapbooks, photographs, and other papers relating primarily to the National Archives where Hyde served as director of archival service from 1934 to 1942. Includes papers concerning Hyde's college years and manuscripts of his unpublished poetry written under the pen name of Edward Ramos. Also includes correspondence and manuscripts of the unpublished poetry of Curtis Hidden Page.
Librarian and archivist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hyde family; United States. -- National Archives and Records Service; American poetry; Archivists; Librarians